Therapeutic plasma exchange in autoimmune diseases: a retrospective study in a tertiary pediatric hospital in Mexico - Menchaca-Aguayo, Héctor; Alpízar-Rodríguez, Deshire; León-Rodríguez, Candy; Gutiérrez-Hernández, Rita; Faugier-Fuentes, Enrique (Frontiers in Pediatrics, 2025)
ObjectiveTo describe the use and mortality-associated factors of therapeutic plasma exchange (TPE) in children with autoimmune diseases at a tertiary pediatric hospital in Mexico.MethodsRetrospective cross-sectional study including patients under 18 years old with autoimmune diseases who underwent TPE between 2022 and 2025 at the Hospital Infantil de México Federico Gómez. Demographic, clinical, therapeutic, and laboratory data were analyzed. Clinical response and mortality-associated factors were assessed.ResultsForty-one patients were included (68% female; median age: 12 years). The most frequent indications for TPE were systemic lupus erythematosus (SLE) (56.1%) and autoimmune encephalitis (14.6%). Other diagnoses included macrophage activation syndrome (MAS) (n = 3), overlap syndromes (n = 3), juvenile dermatomyositis (n = 2), and single cases of ANCA-associated vasculitis, Takayasu arteritis, antiphospholipid syndrome (APS), and Kawasaki disease. Complete or partial remission was achieved in 85.4% of cases, with variable responses depending on the underlying condition. TPE was well tolerated, with few adverse events. Overall mortality was 14.6% (n = 6), all due to sepsis (p < 0.001). Deceased patients had higher pre-TPE levels of CRP, procalcitonin, and ferritin, though not statistically significant. Longer disease duration was significantly associated with increased mortality in both univariable (OR 1.05, 95% CI 1.01–1.10; p = 0.04) and multivariable analysis adjusted for age, sex, and SLE diagnosis (OR 1.06; 95% CI 1.01–1.14; p = 0.04). Among SLE patients without sepsis, MEX-SLEDAI scores improved significantly.ConclusionTPE was safe and beneficial in children with severe autoimmune diseases. Mortality was related to disease duration rather than the procedure itself.